Novel sulindac derivatives: synthesis, characterisation, evaluation of antioxidant, analgesic, anti-inflammatory, ulcerogenic and COX-2 inhibition activity - Mashooq A. Bhat; Mohamed A. Al-Omar; Nawaf A. Alsaif; Abdulrahman A. Almehizia; Ahmed M. Naglah; Suhail Razak; Azmat Ali Khan; Naeem Mahmood Ashraf (Taylor & Francis Group, 2020)
A new series of N'-(substituted phenyl)-2-(1-(4-(methylsulfinyl) benzylidene)−5-fluoro-2-methyl-1H-inden-3-yl) acetohydrazide derivatives (1 - 25) were prepared in good yields in an efficient manner. All the compounds were fully characterised by the elemental analysis and spectral data. Synthesised compounds were evaluated for antioxidant activity by DPPH method. Compounds 7 (R = 3-methoxyphenyl), 3 (R = 4-dimethylaminophenyl) and 23 (R = 2,4,5-trimethoxy phenyl) substitutions were found to be having highly potent antioxidant activity. Compound 3, with para dimethylaminophenyl substitution was found to be having highest antioxidant activity. It was further evaluated in vivo for various analgesic, anti-inflammatory, ulcerogenic and COX-2 inhibitory activity in different animal models. Lead compound 3 was found to be significant anti-inflammatory and analgesic agent. It was also evaluated for ulcerogenic activity and demonstrated significant ulcerogenic reduction activity in ethanol and indomethacin model. The LD50 of compound 3 was found to be 131 mg/kg. The animals treated with compound 3 prior to cisplatin treatment resulted in a significant reduction in COX-2 protein expression when compared to cisplatin-treated group. Sulindac derivative with para dimethylaminophenyl substitution was found to be the most potent antioxidant, anti-inflammatory and analgesic agent as well as with significant gastric sparing activity as compared to standard drug sulindac. Compound 3 significantly downregulated liver tissue COX‐2 gene expression.